Industrial, Biological and Pharmacological uses of Shorea macrophylla L. - Ahmad, Husaini; Samuel, Lihan; Ajibola, Olaide Olawunmi; Rosmawati, Saat; Ngui, Sing Ngieng; Wahab Abideen, Akinkunmi; Fazia, Mohamad Sinang (2021)
Trees of Shorea macrophylla L. (Engkabang jantong) are one of the most valuable commodities in South East Asia, due to their good quality of Meranti timbers and illipe nuts that generate oil. They also produced important green industrial chemicals such as varnishes, insecticides, additives in lubricants, adhesives, polishes, plasticizers, and of medicinal values. Several related studies have proven that the wood and wood residues of S. macrophylla L. are suitable for the production of furniture and cattle feedstocks. At the same time, fat emulsion from the illipe nuts attracts more attention in the waxes and cosmaceutical as well as food products industries. Similarly, it has been employed as an active natural food additives in a few newly produced food products. These makes S. macrophylla L. an important commodity in foreign markets. In order to better unravel the potentials of this plant, further in depth studies would be required. Therefore, the purpose of this article is to review on the industrial, biological, and pharmacological applications of S. macrophylla.